Methodology and Diagnostics of Digital Transformation in the Structures of the State Administration - Andriyana Andreeva; Oleg Asenov (Business & Management Compass)
This work is devoted to the study of the methodological aspects for diagnosing the processes of providing e-services in the structures of the state administration and assessing the symmetry for the penetration of digitalization in terms of internal interactions and processes providing content for the presentation of e-services.